The Actualization of Pancasila from the Legal Perspective within the Academic Environment of University. - Ernia Duwi Saputri; Sely Ayu Lestari (Jurnal Pendidikan Edutama, 2024)
The individuals within the university community, encompassed in the academic society, constitute a vital component of the nation that functions as supporters of Pancasila values. Indonesia as a nation that acknowledges God, emphasizes humanity, unity, democracy, and social justice, regards Pancasila as a valuable foundation. This research aims to elucidate how Pancasila should be actualized within the educational environment, particularly from a legal perspective, focusing on IKIP PGRI Bojonegoro. The research question is: "How is the actualization of Pancasila in the legal perspective within the university environment?" This study adopts a qualitative research approach, utilizing data collection methods such as interviews and documentation. The findings indicate that the societal order, especially within the university environment, needs to reflect Pancasila's values in daily life. As students equipped with knowledge and technology, coupled with a profound intellectual sense, they can leverage their capabilities and the support provided by the academic institution to collectively achieve shared goals.